2020
DOI: 10.3390/pathogens9020096
|View full text |Cite
|
Sign up to set email alerts
|

Map3k14 as a Regulator of Innate and Adaptive Immune Response during Acute Viral Infection

Abstract: The replication of virus in secondary lymphoid organs is crucial for the activation of antigen-presenting cells. Balanced viral replication ensures the sufficient availability of antigens and production of cytokines, and both of which are needed for virus-specific immune activation and viral elimination. Host factors that regulate coordinated viral replication are not fully understood. In the study reported here, we identified Map3k14 as an important regulator of enforced viral replication in the spleen while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Mutations in the NFκB pathway leads to dependence of MAP3K14, both in vitro and in vivo, suggesting that MAP3K14 is potentially a therapeutic target in MCL [124]. Additionally, MAP3K14 has been identified to be a regulator of the innate and adaptive immune responses with mutations leading to atypicalcombined immunodeficiency [125,126]. The mRNA expression of MAP3K14 was associated with increased survival in breast cancer, cervical squamous cell carcinoma, head-neck squamous cell carcinoma, pancreatic ductal adenocarcinoma, rectum adenocarcinoma, sarcoma, and thyroid carcinoma.…”
Section: Map3k14mentioning
confidence: 99%
“…Mutations in the NFκB pathway leads to dependence of MAP3K14, both in vitro and in vivo, suggesting that MAP3K14 is potentially a therapeutic target in MCL [124]. Additionally, MAP3K14 has been identified to be a regulator of the innate and adaptive immune responses with mutations leading to atypicalcombined immunodeficiency [125,126]. The mRNA expression of MAP3K14 was associated with increased survival in breast cancer, cervical squamous cell carcinoma, head-neck squamous cell carcinoma, pancreatic ductal adenocarcinoma, rectum adenocarcinoma, sarcoma, and thyroid carcinoma.…”
Section: Map3k14mentioning
confidence: 99%
“…T-cells lacking NIK exhibited reduced antigen responses, cytokine activation, and altered cytoskeletal dynamics compared to wild-type cells [ 29 ]. Indeed, reduced antiviral CD8 + T-cell immunity was observed in Map3k14 aly/aly mice infected with lymphocytic choriomeningitis virus (LCMV) [ 30 ]. In another study, a T cell-intrinsic requirement for NIK was found in graft versus host disease (GVHD), whereby NIK-deficient T-cells transferred to major histocompatibility complex (MHC) class II mismatched mice failed to induce GVHD [ 31 ].…”
Section: Nik Regulation Of Lymphoid Organogenesis Immune Cell Devmentioning
confidence: 99%
“…In addition to the aberrant development and paucity of B-cells, including marginal zone B-cells in Map3k14 aly/aly mice, a lack of CD169 + macrophages was also observed, whereas other macrophage populations were not affected [ 30 ]. As macrophages are potent immunoregulatory cells of the innate immune system that fight pathogens, the loss of CD169 + macrophages was directly correlated with reduced immune activation in response to vesicular stomatitis virus (VSV) or lymphocytic choriomeningitis virus (LCMV) infection [ 30 ]. In another study, the sine oculis homeobox (SIX) homologue family transcription factors SIX1 and SIX2, which are developmentally silenced, were shown to function as negative regulators of noncanonical NF-κB signaling.…”
Section: Nik Regulation Of Lymphoid Organogenesis Immune Cell Devmentioning
confidence: 99%
“…NIK phosphorylates Inhibitor of κB-kinase-α (IKKα), to trigger p100 processing to p52 and generation of transcriptionally active p52-RelB complexes [19][20][21][22] . As an activator of a conserved immune pathway, NIK has been documented to have critical roles in B-cell, lymphocyte, and lymph node development, along with other immune functions such as immunoglobulin production and T-cell function 19,[23][24][25][26][27] . Furthermore, more studies have highlighted important NF-κB-independent metabolic functions for NIK including roles in mitochondrial dynamics, metabolic reprograming under nutrient stress in cancer cells, as well as regulation of glycolysis in T-cells [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…NIK has critical roles in B-cell, lymphocyte, and lymph node development, immunoglobulin (Ig) production and T-cell function. Consequently, Nik aly mutant mice (aly; alymphoplasia), which lack NIK activity, and NIK knockout mice (NIK KO) exhibit lymphopenia, abnormal Peyer's patches, aberrant splenic and thymic structures, reduced B-cell numbers and Ig serum levels leading to humoral immunodeficiency [1,[5][6][7][8][9]. In humans, NIK loss-of-function mutations were recently identified in patients with primary immunodeficiency (PID) who exhibit similar immune defects as Nik aly and NIK KO mice [10,11], demonstrating the relevance of NIK deficient mouse models for immunodeficiency disease.…”
Section: Introductionmentioning
confidence: 99%